Alternatif Fondasi Tiang Pancang Pada Gedung Pengendalian Penduduk dan Keluarga Berencana (P2KB) Palu - Hidayat, R.; Irdhiani, Irdhiani (Civil Engineering Department, Tadulako University, 2021)
The foundation design of Pengendalian Penduduk dan Keluarga Berencana is located on Jl. R.A. Kartini No. 100, Palu City, Central Sulawesi. In field testing using 2-point of (CPT), the value of hard-ground support at 8 – 9 m below the surface and the loads of building structures of 2 (two) floor buildings that work on the foundations are quite large, this is a consideration in choosing the type of used foundation. The point of this design is to obtain the dimensions of the pile foundation and calculate the bearing capacity of the foundation permit and settlement that meet the safety requirements. The calculation for bearing capacity of the foundation is calculated using (CPT) data and soil shear strength parameter data (c and tetha). Single pile is calculation by using the Semi-Empirical method and using Brooms Method for calculating lateral force on the driven piles. The dimensions of the foundation are planned based on the load (Qv) acting on the entire foundation. Calculation of bearing capacity of a single pile with a penetration depth of 8,20 m and varying dimensions are used in the planning. Based on the calculation of the bearing capacity of a single pile using (CPT) data on the load that works on the foundation, was obtained 25 cm and 30 cm diameter of pile. while the calculation uses ground shear strength parameter data (c and tetha) obtained pile diameter of 30 cm and diameter of 35 cm. Based on the calculation of the bearing capacity of a single pile, the dimensions of the foundation and the settlement in permits has reached the safety requirements.